Sacred Forests and Sustainable Practices: The Role of the Lom Tribe’s Local Wisdom in Disaster Resilience - Ayu Lestari, Zakia; Syafutra, Randi; Rina, Sinta Desta (Global Review of Tourism and Social Sciences, 2025)
This study explores the Lom Tribe’s indigenous knowledge in disaster mitigation, emphasizing their early warning systems, sustainable land management, adaptive architecture, and spiritual beliefs. The findings reveal that the Lom Tribe relies on environmental cues such as bird migration, wind patterns, and water levels to predict natural disasters, while their sacred forest conservation and rotational farming techniques help prevent ecological degradation. Additionally, their stilt house architecture reduces flood risks, and spiritual rituals reinforce environmental responsibility and community resilience. Despite these effective strategies, challenges such as modernization, lack of formal documentation, and policy disconnects hinder integration with formal disaster risk management frameworks. This study contributes to the discourse on traditional ecological knowledge (TEK) and community-based disaster risk reduction (CBDRM), advocating for stronger collaboration between indigenous communities, researchers, and policymakers. Future research should explore comparative studies and policy frameworks to formalize indigenous disaster mitigation within national and regional governance systems.